The Effect of ESG Performance and Profitability on Company Value with Audit Quality as a Moderation Variable (Empirical Study on Energy Sector Companies Listed on the IDX and BGK Foundation's ESG Index in 2020-2022) - Juanita Agustina Renaldy; Puspita Rani (Journal Research of Social Science, Economics, and Management, 2025)
Companies listed on the stock exchange are required to publicly disclose reports such as annual and financial statements through the Indonesia Stock Exchange (IDX) authority and their respective company websites for investors and potential investors. This study aims to analyze and empirically test the effect of ESG performance and profitability on firm value, with audit quality as a moderating variable, in companies listed on the IDX and the ESG Index BGK Foundation in 2020–2022. This quantitative research applies the Moderated Regression Analysis (MRA) method, processed using Eviews 12. The population in this study consists of energy sector companies, with a sample of 19 firms. Based on the study’s results, it was found that ESG performance has a negative effect on company value, while profitability has no significant effect on company value. The results of the moderation test indicate that the audit quality variable weakens the negative effect of ESG performance on firm value; however, audit quality does not moderate the effect of profitability on firm value. The implications of this study highlight that, while ESG initiatives are crucial for long-term sustainability, excessive costs or limited market understanding of ESG practices may initially reduce firm value—particularly in developing markets where investors still prioritize short-term profitability.